Influence of Enzyme Concentration and Hydrolysis Time on Soluble Protein Content of Protein Hydrolysate Prepared from Apple Snail (Pila ampullacea) - Andre Yusuf Trisna Putra; Dedin Finatsiyatull Rosida; Anugerah Dany Priyanto (Engineering Faculty, University of Pembangunan Nasional Jawa Timur, 2021)
The objective of this study was to evaluate soluble protein content of protein hydrolysates obtained by enzymatic hydrolysis of apple snail using a trypsin enzyme. Apple snail were collected from traditional market at Pabean-Sidoarjo. Trypsin enzyme was used in enzymatic hydrolysis. The two variables, enzyme/substrate (E/S) ( 0.01, 0.05, 0.1) ratio and hydrolysis time (3 h, 6 h, 9 h, 12 h, 15 h, 18 h) and was used to produce the apple snail hydrolysate. The result showed that soluble protein content was about 2.3%-4.52%. The increase E/S ratio and hydrolysis time, the higher soluble protein content values was. The highest total soluble protein was achieved E/S 0.1 ratio at 12 h, 4.52%. But, after 12 h hydrolysis time, soluble protein was decreased. Optimum treatment to hydrolyzing apple snail using trypsin enzyme was E3H4 treated (E/S 0.1 ratio and 3 h)